2011
DOI: 10.1038/ncomms1479
|View full text |Cite
|
Sign up to set email alerts
|

Detecting inertial effects with airborne matter-wave interferometry

Abstract: Inertial sensors relying on atom interferometry offer a breakthrough advance in a variety of applications, such as inertial navigation, gravimetry or ground- and space-based tests of fundamental physics. These instruments require a quiet environment to reach their performance and using them outside the laboratory remains a challenge. Here we report the first operation of an airborne matter-wave accelerometer set up aboard a 0g plane and operating during the standard gravity (1g) and microgravity (0g) phases of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
337
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 340 publications
(359 citation statements)
references
References 31 publications
3
337
0
Order By: Relevance
“…These parameters can be easily deduced by fitting the sinusoidal fringes, scanned either by the Raman frequency ramp α in a low vibration environment or by the vibrations themselves, where in that case, the atom sensor is correlated with a mechanical accelerometer. The probability density function [33] of the atom interferometer measurements can also give access to this parameters. A last method can be to simply derive the fringe amplitudes and offsets from the mean value and the standard deviation of the probability density function without any fitting method.…”
Section: Differential Phase Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters can be easily deduced by fitting the sinusoidal fringes, scanned either by the Raman frequency ramp α in a low vibration environment or by the vibrations themselves, where in that case, the atom sensor is correlated with a mechanical accelerometer. The probability density function [33] of the atom interferometer measurements can also give access to this parameters. A last method can be to simply derive the fringe amplitudes and offsets from the mean value and the standard deviation of the probability density function without any fitting method.…”
Section: Differential Phase Extractionmentioning
confidence: 99%
“…In order to * alexis.bonnin@onera.fr improve the sensitivity of atom accelerometers, several projects under development aim to compare the free fall of two different atomic species during few seconds, as the sensitivity scales quadratically with the interrogation time, in 10-m-tall atomic fountains [29][30][31], drop towers [32], sounding rockets, parabolic flights [33] and in space [34][35][36]. These projects are developed in parallel with works on the increase of the momentum transfer [37][38][39][40] to enhance the enclosed area and further improve the interferometers sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…These successes have spurred interest in transitioning cold atom devices from the lab to more demanding environments [9][10][11][12][13][14][15][16][17]. Recently, a three dimensional grating magneto-optical trap (3D GMOT) was demonstrated that satisfies many needs of a deployable system [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, atom interferometry experiments were developed for various applications like precision measurement of fundamental constants [1,2], gravimetry [3], gradiometry [4] or inertial sensing [5,6]. Based on this methods, cold atoms sensors measure interferometrically the inertial effects affecting the experiment with respect to free falling laser-cooled atoms that are split and recombined using two counter-propagating laser beams.…”
Section: Introductionmentioning
confidence: 99%